Methods for Selection of Network Security Systems in accordance with Information Security Policies - Dmitry Sergeevich Chernyavskiy (Безопасность информационных технологий, 2015)
Selection of network security systems (NSS) that are sufficient for implementation of information security (IS) policies is one of the major steps of IS policy management process. The paper describes existing methods for selection of NSS, outlines their peculiarities and drawbacks, and presents a method for selection of NSSs, which takes into account their cost.